2020
DOI: 10.1038/s41467-020-18147-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinically applicable histopathological diagnosis system for gastric cancer detection using deep learning

Abstract: The early detection and accurate histopathological diagnosis of gastric cancer increase the chances of successful treatment. The worldwide shortage of pathologists offers a unique opportunity for the use of artificial intelligence assistance systems to alleviate the workload and increase diagnostic accuracy. Here, we report a clinically applicable system developed at the Chinese PLA General Hospital, China, using a deep convolutional neural network trained with 2,123 pixel-level annotated H&E-stained whole sli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
116
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(116 citation statements)
references
References 29 publications
0
116
0
Order By: Relevance
“…Haematoxylin-eosin (H&E) staining is the most common method for discriminating benign and malignant lesions. For GC, most studies used CNN models to construct diagnostic systems for H&E staining[ 13 - 17 ]. In 2017, Sharma et al [ 17 ] reported the first study about computer-aided classification in H&E staining of GC.…”
Section: Achievements Of Ann Research In Gi Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Haematoxylin-eosin (H&E) staining is the most common method for discriminating benign and malignant lesions. For GC, most studies used CNN models to construct diagnostic systems for H&E staining[ 13 - 17 ]. In 2017, Sharma et al [ 17 ] reported the first study about computer-aided classification in H&E staining of GC.…”
Section: Achievements Of Ann Research In Gi Diseasesmentioning
confidence: 99%
“…Rapid progress has been made during the past three years. A CNN model fed by over 2000 H&E slide images achieved a near 100% sensitivity and 80.6% specificity[ 13 ]. Such optimal sensitivity showed that this model has potential in preliminary screening of H&E staining.…”
Section: Achievements Of Ann Research In Gi Diseasesmentioning
confidence: 99%
“…A number of recent studies have paid attention to lesion detection, classification and characterization in this anatomic site. For instance, Song et al [ 84 ] developed and trained a deep CNN to differentiate between benign and malignant gastric tumors, with a sensitivity of 100% and a specificity of 80.6%[ 84 ]. Also, a network developed by Sharma et al [ 85 ] classified gastric cancer cases according to immunohistochemical response and presence of necrosis, with accuracy rates of 0.699 and 0.814, respectively[ 85 ].…”
Section: Applications Of Ai In Gi Pathologymentioning
confidence: 99%
“…As shown in Figure 1 , we used the DeepLab v3 image segmentation model with ResNet-50 to establish the GD system. [ 4 ] During the model training process, the parameters of the gastric cancer detection model [ 5 ] were used as the initial values, and the model parameters were fine-tuned using the prostate training data by transfer learning. The model training was performed with TensorFlow on 8 NVIDIA GTX1080Ti GPUs.…”
mentioning
confidence: 99%
“…We also applied histopathological-oriented data augmentation. [ 5 ] The slide-level prediction was defined as the average of the top 100 probabilities of the pixel-level predictions.…”
mentioning
confidence: 99%